The influence of firm and industry political spending on tax management among S&P 500 firms - Minnick, Kristina; Noga, Tracy (Journal of Corporate Finance, 2017)
Political expenditures are made by corporations to potentially influence legislators, regulators, and to encourage favorable outcomes for the corporation, such as policies which help reduce their corporate taxes. Using political spending data from Opensecrets.org, we examine whether S&P 500 firms that invest in political spending or are in industries with trade associations that invest in political spending accrue greater future tax benefits. Controlling for endogeneity, we first show that companies do not necessarily need to politically spend themselves; instead they can benefit from lower taxes from a spillover effect from trade group contributions. However, the benefit is not as large as if the firm contributed themselves. Companies benefit from investing in political spending by reducing both their Generally Accepted Accounting Principles (GAAP) and Cash ETRs, particularly if the firms use think tank and lobbying contributions which focus on tax issues. However, trade group contributions should focus on political contributions to candidates, particularly if those candidates are members of the Senate Finance or House Ways and Means committees. Finally, although there is a trailing effectiveness of political spending, a company needs to maintain it's spending in order to maintain the same level of tax savings as they have enjoyed in the past. The results are robust to a number of additional tests to control for causality and endogeneity. Overall, these results give additional insight into better understanding how different forms of political spending can benefit companies by lowering taxes.